SUBSTITUSI TEPUNG LABU KUNING (Cucurbits moschata, Durch) TERHADAP KANDUNGAN VITAMIN A DAN DAYA TERIMA PANELIS PADA SOSIS IKAN NILA (Oreochromis niloticus) - Fu’ad Hasyim Asngari; Agustiana Agustiana; Hafni Rahmawati (Fish Scientiae, 2019)
Pumpkin is vegetable that rich in beta carotene as a precursor of vitamin A.Pumpkin can be processed into flour, which is then substitution on fish sausage products to improve the nutritional value. The purpose of this study was get precise percentage substitution of pumpkin flour, to know the effect of pumpkin flour substitution on the content of vitamin A and the panelist acceptance on tilapia sausage product. The firststage was manufacturing of pumpkin flour with drying using sunlight for 2-3 days, followed by the process of flouring. The next pumpkin flour in substitution on the tilapia sausage with a percentage 0%, 10%, 15% and 20% of the total fish sausage batter. This study uses a completely randomized design (CRD) with 4 treatments and 3 replications.The results showed that tilapia fish sausage with 20% substitution of pumpkin flour is thebest treatment in terms of the vitamins A content. Percentage substitution of pumpkin flour may increase vitamin A content in tilapia fish sausage. The content vitamin A tilapia fish sausage with substitution of pumpkin flour with a percentage of 0%, 10%, 15% and20% consecutively are <0.01 mg / g, 0.9825 ug / g, 1.5025 ug / g and 1.5375 ug / g. The organoleptic test results showed that panelists acceptance on tilapia fish sausage with substitution of pumpkin flour ranging between 5 (rather like) up to 6,8 (like).